A novel approach to fabricate load-bearing Ti6Al4V-Barium titanate piezoelectric bone scaffolds by coupling electron beam melting and field-assisted sintering. (January 2023) - Riaz, Abdullah; Polley, Christian; Lund, Henrik; Springer, Armin; Seitz, Hermann
Graphical abstract: Highlights: Electron beam melting and field-assisted sintering were coupled to fabricate load-bearing Ti6Al4V-BaTiO3 piezoelectric bone scaffolds. Images of sintered composite scaffold interface revealed that the Ti6Al4V cylindrical lattice structure bounded with BaTiO3 matrix without its major deformation. The fabricated Ti6Al4V-BaTiO3 scaffold showed a piezoelectric response of (0.63 ± 0.12) pC/N without poling which increased to (4.92 ± 0.75) pC/N after corona poling. Nanoindentation values reveal that Ti6Al4V is the harder and stiffer part of the Ti6Al4V-BaTiO3 scaffold. Abstract: A critical-size bone defect in load-bearing areas is a challenging clinical problem in orthopaedic surgery. Titanium alloy (Ti6Al4V) scaffolds have advantages because of their biomechanical stability but lack electrical activity, which hinders their further use. This work is focused on the fabrication of Ti6Al4V-Barium Titanate (BaTiO3 ) bulk composite scaffolds to combine the biomechanical stability of Ti6Al4V with electrical activity through BaTiO3 . For the first time, a hollow cylindrical Ti6Al4V is additively manufactured by electron beam melting and combined with piezoelectric BaTiO3 powder for joint processing in field-assisted sintering. Scanning electron microscope images on the interface of the Ti6Al4V-BaTiO3 composite scaffold showed that after sintering, the Ti6Al4V lattice structure bounded with BaTiO3 matrix without its major deformation. The Ti6Al4V-BaTiO3 scaffold had average piezoelectric constants of (0.63 ± 0.12) pC/N directly after sintering due to partial dipole alignment of the BaTiO3 tetragonal phase, which increased to (4.92 ± 0.75) pC/N after a successful corona poling. Moreover, the nanoindentation values of Ti6Al4V exhibited an average hardness and Young's modulus of (5.9 ± 0.9) GPa and (130 ± 14) GPa, and BaTiO3 showed (4.0 ± 0.6) GPa and (106 ± 10) GPa, respectively. It reveals that the Ti6Al4V is the harder and stiffer part in the Ti6Al4V-BaTiO3 composite scaffold. Such a scaffold has the potential to treat critical-size bone defects in load-bearing areas and guide tissue regeneration by physical stimulation.